HYPOCRYSIS IN THE SHORT STORY ENTITLED AKHIRNYA KITA SEMUA MENJADI MALING BY ZAIDINOOR - Christina Wahyuningsih; Harjito; Ika Septiana (Universitas Negeri Yogyakarta, 2024)
Hypocrisy in literature often reflects the complexity of human nature as well as broader social dynamics, providing critical insight into culture and social structure. This research aims to identify human nature and broader social dynamics, and describe hypocrisy in the short story